A Simple and Cost Effective Data Acquisition System for Mobile Satellite Experimental Work under Treeshadowed and Building-shadowed - Bong, V.P.; Abidin, W.A.W.Z; Abba, I.; Othman, A.K.; Zen, H.; Masri, T. (IEEE, 2010)
Signal degradation in Mobile Satellite (MS) is due to several factors such as ionospheric effect, multipath fading, treeshadowed and building-shadowed. This affects the Mobile Satellite Service (MSS) to provide continuous communication service to the users. Since there is not adequate data available on the signal performance of the MS in the Asian continent, thus, an experimental work is essential to be carried out to investigate the effect of factors such as the tree-shadowed and buildingshadowed on the signal strength. This paper discusses the cost effective set up. It can be used to measure the effect of trees and buildings on the received mobile satellite signal operating in the L-band. The methodology uses to carry up the experimental works is discussed in detail. The measurements of the signal performance are performed under different MS environments such as tree-shadowed and building-shadowed and hence the results are compared to the data obtained for open space environment. The analysis of the signal performance under different MS environments is performed with respect to the elevation and azimuth degree at different time under a clear sky condition. The analysis produced forms an important part in the studies of the signal performance. From this research work, we would like to propose a simple and low cost data acquisition system in order to encourage more experimental works to be carried out especially in the less developed countries.